If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3xy + 5z)(3xy + 5z) = 0 Multiply (3xy + 5z) * (3xy + 5z) (3xy * (3xy + 5z) + 5z * (3xy + 5z)) = 0 ((3xy * 3xy + 5z * 3xy) + 5z * (3xy + 5z)) = 0 Reorder the terms: ((15xyz + 9x2y2) + 5z * (3xy + 5z)) = 0 ((15xyz + 9x2y2) + 5z * (3xy + 5z)) = 0 (15xyz + 9x2y2 + (3xy * 5z + 5z * 5z)) = 0 (15xyz + 9x2y2 + (15xyz + 25z2)) = 0 Reorder the terms: (15xyz + 15xyz + 9x2y2 + 25z2) = 0 Combine like terms: 15xyz + 15xyz = 30xyz (30xyz + 9x2y2 + 25z2) = 0 Solving 30xyz + 9x2y2 + 25z2 = 0 Solving for variable 'x'. Factor a trinomial. (3xy + 5z)(3xy + 5z) = 0Subproblem 1
Set the factor '(3xy + 5z)' equal to zero and attempt to solve: Simplifying 3xy + 5z = 0 Solving 3xy + 5z = 0 Move all terms containing x to the left, all other terms to the right. Add '-5z' to each side of the equation. 3xy + 5z + -5z = 0 + -5z Combine like terms: 5z + -5z = 0 3xy + 0 = 0 + -5z 3xy = 0 + -5z Remove the zero: 3xy = -5z Divide each side by '3y'. x = -1.666666667y-1z Simplifying x = -1.666666667y-1zSubproblem 2
Set the factor '(3xy + 5z)' equal to zero and attempt to solve: Simplifying 3xy + 5z = 0 Solving 3xy + 5z = 0 Move all terms containing x to the left, all other terms to the right. Add '-5z' to each side of the equation. 3xy + 5z + -5z = 0 + -5z Combine like terms: 5z + -5z = 0 3xy + 0 = 0 + -5z 3xy = 0 + -5z Remove the zero: 3xy = -5z Divide each side by '3y'. x = -1.666666667y-1z Simplifying x = -1.666666667y-1zSolution
x = {-1.666666667y-1z, -1.666666667y-1z}
| 12=11d-2d^2 | | (3a-5b)(3a-5b)= | | 5.6+3= | | x^2+35=12x-1 | | 9-a=11-2a | | (2x+3y)(2x+3y)= | | 9=6a-27 | | 2k^2+9=-7 | | (9x-2)(9x-2)= | | 5-8X=55-43X | | (T)(3)=-15 | | -91-10X=9X+23 | | A=ax(2)+bx+c | | 6X+5=-125-7X | | 7b+3(b-1)+3=2(b+18) | | -41-3x=8-10x | | 16x^4-20x^2+5=0 | | 6x^2-600=0 | | 5x=7x-10 | | 2x^2-15x-8=0 | | 6x+7=5x+15 | | -8-9=-8(x-9) | | 64x-1=0 | | 2x+107=10x-5 | | 2x^6+4x^5-6x^4+4x^3= | | 4x-y=-1 | | 73-3x=15x+17 | | 3x-4(1-x)=4+5x | | 15x^2+27x-2=0 | | 8(x+2)-10=3(2x-1)+9 | | 12b-8= | | 11x-8x=156-43x |